QUALITY OF DIRECT CUSTOMER COMPLAINTS SERVICE IN DELTA TIRTA REGIONAL DRINKING WATER COMPANIES IN SIDOARJO DISTRICT, SIDOARJO REGENCY - Reyndi Rusmanjaya; Agus Widiyarta (DIA: Jurnal Administrasi Publik, 2021)
The quality of public services can be used as a benchmark for the results of the government's performance itself has been going well or there are still things that need to be addressed. Clean water service is a product of the type of service goods that are grouped in the form of provision or management of a physical form including distribution and direct delivery to consumers in one system. PDAM "Delta Tirta" Sidoarjo District, Sidoarjo Regency is very concerned about service performance aspects to maintain continuous service continuity, but there are still complaints. The purpose of this research is to find out how the quality of service for customer complaints directly to the Regional Water Company (Pdam) Delta Tirta in Sidoarjo District, Sidoarjo Regency. The type of this research is descriptive qualitative with data collection techniques in the form of interviews, observation, documentation, and literature study. To determine the quality of service directly at PDAM Delta Tirta, Sidoarjo District, Sidoarjo Regency at this time, researchers chose to use the 5 dimensions of public service quality proposed by Zeithaml et al 1990 in Hardiyansyah (2011:4647), namely Tangibel (Intangible), Reliability (Reliability), Responsiveness (Response), Assurance (Assurance), and Empathy (Empathy). Sources of data used are informants and documents related to research. The results of this study indicate that based on the five dimensions of service quality according to Parasuraman, including physical evidence (tangibles), reliability (reliability), responsiveness (responsiveness), assurance (assurance), and empathy (empathy), it can be concluded that PDAM Delta Tirta Sidoarjo District, Sidoarjo Regency has fulfilled these five dimensions and has good service quality.